PKM MEWUJUDKAN KELUARGA BERKUALITAS MELALUI UPAYA PENCEGAHAN STUNTING DENGAN PEMBUATAN MAKANAN SEHAT DAN BERGIZI “ OLAHAN NAGET TEMPE” DI KELURAHAN TANJUNG RHU - Rahmi Pramulia Fitri; Fitri Silvia; Rahmah Datul Dina; Nur Amelia (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Tempeh is a fermented food from soybeans (Glicyne max) with the help of microorganisms Rhizopus sp, which is currently starting to be developed by utilizing other types of raw materials. This review was conducted to understand the potential of tempeh fermented local food related to efforts to reduce stunting rates in Indonesia. There has been a lot of development of fermented tempeh food apart from soybeans. The fermentation process tends to increase macro and micronutrients needed by the body to support optimal growth so that in the end it can prevent stunting. The purpose of this service is an effort to prevent stunting from an early age and provide an understanding to the community in Tanjung Rhu village that diet is a factor in the high level of stunting. The result of this service is the increase in enthusiasm and increasing public understanding of stunting and diet for stunting prevention, one of which is the activity of making processed tempeh nuggets